Risk factors and outcome of bacterial infections in cirrhosis - Bruns, Tony (Baishideng Publishing Group Co., Limited, 2014)
Viable and non-viable pathological bacterial translocation promote a self-perpetuating circle of dysfunctional immune activation and systemic inflammation facilitating infections and organ failure in advanced cirrhosis. Bacterial infections and sepsis are now recognized as a distinct stage in the natural progression of chronic liver disease as they accelerate organ failure and contribute to the high mortality observed in decompensated cirrhosis. The increasing knowledge of structural, immunological and hemodynamic pathophysiology in advanced cirrhosis has not yet translated into significantly improved outcomes of bacterial infections over the last decades. Therefore, early identification of patients at the highest risk for developing infections and infection-related complications is required to tailor the currently available measures of surveillance, prophylaxis and therapy to the patients in need in order to improve the detrimental outcome of bacterial infections in cirrhosis.